Growth and grain yield response of maize (zea mays) to water and nitrogen in small holder irrigation schemes in the Limpopo Province - Modiba, Matlakala Dinah (My University, 2002)
Refer to document
Thesis (M. Sc. (Agricultural Management)) -- University of LImpopo, 2002
Keywords: Crops; Nitrogen fertilizer; Irrigation; Grain yields; Corn -- Yields; Grain -- Irrigation